Nationless States and Stateless Beings: The politics of identity and citizenship in Claudio Mir’s Mondongo Scam and Cheech Marin’s Born in East L.A. - Rebecca A Barnes (Vernacular: New Connections in Language, Literature, & Culture, 2022)
In the colloquial sense of the term, the word citizen refers to an individual who belongs to a nation, either by birthright or by naturalization. Therefore, citizenship denotes a political and a social belonging, an ideological home, and, in most cases, a strong foundation for the development of one’s personal identity. However, since nations are inherently artificial structures, made only tangible in the present day by a few centuries of recorded history, a philosophical approach to the term citizen complicates this definition. Based off critics including Hannah Arendt, Homi Bhabha, Fernando Ortiz, and Jacques Derrida, this essay seeks to explore the philosophical underpinnings of citizenship and how, especially amongst the Latin American characters in certain works, the politics of exclusion and demonization create a cultural vacuum on the individual level that destabilizes the entire nation-state system and blurs the meaning of belonging. Overall, the argument is structured as a comparison of Claudio Mir’s play Mondongo Scam and Cheech Marin’s film Born in East L.A. The analysis of Mir’s play bases itself off the exploration of its title, and how, despite wanting to be a taxpaying, hardworking U.S. citizen who would contribute to the wellbeing of his adopted nation, Casiano finds himself in a parasitic relationship with the U.S., ultimately losing himself through a process of severe acculturation. On the other hand, Marin’s film serves both as comic relief and as an inversion of this existential struggle, seeing as Rudy is a U.S. citizen forced to face the importance of the Latin American portion of his identity, which he has tried to escape his entire life. Together, these works demonstrate not only that citizenship is not dictated by borders, but also that it cannot be defined by something as material as legal documentation.
Keywords: diasporic studies; citizenship; migrant condition; cultural studies